Outcomes of a harm reduction shared learning intervention Pilot in the U.S. South. Issue 3 (2nd October 2022) - McCormick, Katie A.; Stanton, Megan; Ali, Samira; Chavez, Sandra
Abstract: The U.S. South is disproportionately burdened by the HIV and opioid epidemics, hastening the need for effective multi-level, person-centered approaches, such as harm reduction. LEARN HR is a shared learning intervention that aims to build the harm reduction capacity of HIV service providers and their organizations. This study used a sequential explanatory mixed methods design to examine program evaluation data of two LEARN HR pilot cohorts to (1) assess the preliminary effectiveness of LEARN HR, (2) examine the impact on HIV service providers and their organizations, and (3) examine challenges to adopting harm reduction approaches. Quantitative findings revealed statistically significant increases in HR-related knowledge, attitudes, and skills. Qualitative findings revealed meaningful individual- and organizational-level changes. Findings indicate that LEARN HR was successful in facilitating provider-level changes in knowledge, attitudes, and skills which facilitated sustainable organizational changes.